Build and complete fences and related works at Pejabat Pertubuhan Peladang kawasan C-II Kerpan, Wilayah II, MADA / Muhammad Hazim Che Zaim - Che Zaim, Muhammad Hazim (Universiti Teknologi MARA, Perak, 2022)
Fences are one of the most important safety structure elements for a building. A fence plays several functions in the securities measurements and these functions need to be fully understood in order to create suitable and comfortable building as well as providing privacy also as protection from animal and other threats. This report will discuss about procedure and method to build fences. This report was conducted for Pertubuhan Peladang Kawasan C-II, Kepan that owned by MADA (Muda Agricultural Development Authority). The objective of this report is to analyze the construction of fences and the way how it carried out. It will focus on the whole process of fences construction and other relatable works. It also investigate the equipment and machinery in the methods of fences construction and to determine the time that have been used for the construction. This report will also look to at the problem and the solution in fences construction that would fulfill the criteria perfect fences that long lasting.